Synthesis ratios of Mg-Al and Zn-Al layered double hydroxides efficiency and selectivity in nitrate removal from solution - M. Mohammadi; A. Mohammadi Torkashvand; P. Biparva; M. Esfandiari (Global Journal of Environmental Science and Management)
Four diverse chlorides layered double hydroxides with diverse ratios, i.e. Mg-Al (3:1), Mg-Al (4:1), Zn-Al (4:1), and Zn-Al (3:1) LDHs, were prepared to evaluate their efficiency and selectivity towards nitrate removal from aquatic solutions. A batch experiment was done at the initial nitrate concentration of 5-1000 mg/L, pH 5 to 12, and contact time of 5-180 min. Isotherms of nitrate adsorption on LDHs, soil and soil-LDH mixtures were studied. Kinetics of adsorption, temperature effect, nitrate adsorption in nitrate adsorption, simulated soil solution and desorption on Mg-Al-LDH (4:1) were measured. At an optimum speed of 250 rpm, pH value of 7 and adsorbent dosage of 2 g/L, the amounts of nitrate adsorption on Mg-Al- LDH (3:1) and Mg-Zn-LDH (3:1) and also on Mg-Al- LDH (4:1) and Mg-Zn-LDH (4:1) were obtained after 30 and 60 min, respectively. Isotherm studies indicated that nitrate adsorption on soil, soil-LDH mixture, and LDH fitted Langmuir linear isotherm. The highest nitrate adsorption on Mg-Al-LDH (4:1) and a mixture of soil-Mg-Al-LDH (4:1) were 188.67 and 107.52 mg/g, respectively. Among the studied kinetic equations for nitrate adsorption on Mg-Al-LDH (4:1), the pseudo-second-order with R2=0.998 had the best fitness. Negative values of ∆H in different nitrate concentrations indicated the exothermic process of nitrate adsorption on Mg-Al-LDH (4:1). In the presence of other anions, Mg-Al-LDH (4:1) removed nitrate preferentially. Moreover, Mg-Al-LDH (4:1) could exchange nitrate 20 times in different concentrations with no reduction in its adsorption capacity.